South Korea Market Potential Analysis for Forestry Products - Anto Purwanto (PT FORMOSA CENDEKIA GLOBAL, 2024)
The use of wood as a high-value product does not stop there. Paper, furniture, carbon, and rubber are examples of other non-wood forestry products that we often encounter in everyday life but come from forests. The purpose of this study is to analyze the potential of the South Korean market for forestry products. In this study, we use qualitative methodology to understand and evaluate the opportunities and problems faced by Indonesian forestry products, as well as the global market potential for these products. The potential for Indonesian wood commodities and wood products to enter the South Korean market which has minimal domestic supply still has great potential. With abundant supply, offering quality, competitive prices and guaranteeing the required legal documents, it is believed that Indonesia has the opportunity to answer the needs of wood and wood products in the South Korean market in the future